Analysis of the mathematics and informatics studies in Vilnius Pedagogical University - Dzemyda, Gintautas; Leonavičius, Gražvydas; Našlėnas, Audrius (Lietuvos matematikos rinkinys, 1998)
The article deals with application of statistical methods (parameter clustering and factor analysis) to discover the knowledge on interaction of disciplines via analysis of the results of examinations. The experiments indicate that interactions of mathematical disciplines with disciplines of informatics are weak. This leads to necessary revision of the programs of studies.